E-cigarette use and intentions to smoke among 10-11-year-old never-smokers in Wales. Issue 2 (22nd December 2014) - Moore, Graham F; Littlecott, Hannah J; Moore, Laurence; Ahmed, Nilufar; Holliday, Jo
Abstract : Background: E-cigarettes are seen by some as offering harm reduction potential, where used effectively as smoking cessation devices. However, there is emerging international evidence of growing use among young people, amid concerns that this may increase tobacco uptake. Few UK studies examine the prevalence of e-cigarette use in non-smoking children or associations with intentions to smoke. Methods: A cross-sectional survey of year 6 (10–11-year-old) children in Wales. Approximately 1500 children completed questions on e-cigarette use, parental and peer smoking, and intentions to smoke. Logistic regression analyses among never smoking children, adjusted for school-level clustering, examined associations of smoking norms with e-cigarette use, and of e-cigarette use with intentions to smoke tobacco within the next 2 years. Results: Approximately 6% of year 6 children, including 5% of never smokers, reported having used an e-cigarette. By comparison to children whose parents neither smoked nor used e-cigarettes, children were most likely to have used an e-cigarette if parents used both tobacco and e-cigarettes (OR=3.40; 95% CI 1.73 to 6.69). Having used an e-cigarette was associated with intentions to smoke (OR=3.21; 95% CI 1.66 to 6.23). While few children reported that they would smoke in 2 years' time, children who had used an e-cigarette were less likely to report that they definitely would not smoke tobacco in 2 years' time and were more likely to say that they might. Conclusions: E-cigarettes represent a new form of childhood experimentation with nicotine. Findings are consistent with a hypothesis that children use e-cigarettes to imitate parental and peer smoking behaviours, and that e-cigarette use is associated with weaker antismoking intentions.